Roles and Challenges of Educators in Inclusive Education and Speciality Schools in Indonesia - Atiek Nilangsari; Syafita Maulidya; Jihan Rahma Indah Puspa Sari; Safi'at Intan Nur Halimah (International Disability Innovation Journal, 2025)
This article discusses the roles, types, competencies and challenges faced by educators in the context of inclusive education and speciality schools in Indonesia. Based on a review of national regulations, educational theory and empirical conditions in the field, educators are required to have adequate professional and social competencies to provide quality education services for all learners, including those with special needs. This paper also examines the gap between policy and implementation in the field and presents strategies for continuous development for educators to improve the quality of inclusive education in Indonesia.